EXPERIMENTAL STUDY ON APPLICATION OF MARBLE WASTE AS CONVENTIONAL AGGREGATE FOR BASE COURSE MATERIALS - Gonfa, Lami Gonfa; Tucay Quezon, Emer Tucay Quezon; Geremew, Anteneh (Journal of Civil Engineering, Science and Technology, 2020)
Recently, highway and construction industries utilize a substantial quantity of conventional aggregates. The increasing demands for conventional aggregate cause an increase in the cost of construction, reduction of natural resource, and continuing deterioration of the earth’s surface. On the other hand, the waste generated from the marble industries during the process of cutting and polishing was increasing day by day all over the world. In Ethiopia, the use of Marble Waste Aggregate materials in road construction as a base course material was not well-known, and it was simply wasted at every place where the marble production was continuing. Therefore, this paper focused on evaluating the possibility of using marble waste aggregate as conventional aggregate in the base course layer of flexible pavements by experimental method. To achieve the objectives of the research, mechanical stabilization and laboratory tests have been carried out at different percentage replacement of Conventional Aggregate by (0%, 20%, 40%, 50%, 60%, 80%, and 100%) of Marble Waste Aggregate weights. Marble wastes materials are collected from Burayyu city, Alisha marble processing industry. The laboratory test results for MWA indicated SG, ACV, AIV, LAA, Flakiness Index , Elongation Index, Plastic Index, Water Absorption, and CBR of 2.74%, 23.63%, 26.21%, 27.03%, 26.48%, 13.29%, Non Plastic, 0.50% and 73.3%, respectively. These test results fulfilled the ERA standard specification for some tests, and it showed marginal quality values to the standard specification for GB2 and GB3 base course materials. CBR and gradation test results shown failure to meet the standard specification. Thus, mechanical stabilization was done to improve the mechanical and physical properties of Marble Waste Aggregate. Blending of 80%MWA with 20% CA results in SG, ACV, AIV, LAA, Flakiness Index, Elongation Index, Plastic Index, Water Absorption, and CBR of 2.83%, 18.2%, 21.52%, 22.58%, 23.79%, 16.29%, Non Plastic, 0.80%,and 82.5% respectively. At this proportion the gradation also observed to fit with the required ERA standard specification of GB2 and GB3 materials. Therefore, the use of marble waste aggregate up to 80% by weight is recommended for road base course layer, when it is found near to the construction site and in places where the materials are abundantly available.